AN APPROACH FOR MIMICKING ROAD PLANNING AND CIRCULATORY SYSTEM IN HUMAN BODY - Nassib, Sherif A; Yousef, Pasent H; Elnawawy, Fatma M (MATTER: International Journal of Science and Technology, 2015)
The idea of mimicking planning structures and human structure is used in this paper in a detailed way. Roads are one important side in planning as it represents the dynamic system through the circulation system. In this paper, there will be an identification to some definitions, hierarchy, and characteristics concerning the roads and street planning and there will be also an identification for the blood circulation in the human body presenting the definitions and hierarchy of blood in the circulatory system. Also, there will be an analyzed part concerning the Mimics concluded from both sections the blood circulation in the human body and the road planning.